Bagaimana Fenomena ‘Marriage is Scary’ dalam Pandangan Perempuan Generasi Z? - Lestari, Melina; Aimma, Sandhian Lasti; Cahyadi, Shafa Fajriandini; Putri, Khaila Alfiory Lestari Legowo; Mustofa, Mona Maimun (Jurnal Bimbingan dan Konseling Ar-Rahman, 2024)
This research aims to examine the views of Generation Z women regarding the "marriage is scary" phenomenon, which reflects their concerns about marriage. The approach in this research is qualitative with a narrative method. Researchers interviewed 10 students from the Guidance and Counseling study program at Universitas Muhammadiyah Prof. DR. HAMKA as a respondent. Researchers asked about the meaning of marriage, issues that make them worry about marriage and their views on the "marriage is scary" phenomenon.  The results of the research show that Generation Z women have a positive view of marriage, namely as a commitment that is full of challenges and concerns about violence that may occur and the increasingly widespread patriarchal culture. Apart from that, generation Z women also value marriage as a forum for personal growth and mutually supportive relationships. The worries they have in a marriage originate from both within themselves and outside themselves. The increasingly growing phenomenon of "Marriage is scary" strengthens their worries and increasingly encourages them to be more selective in finding a partner and to be more mentally prepared to move toward marriage. The implication for premarital guidance and counseling is that preventive services are needed that can resolve concerns about problems in marriage. _____________________________________________________________Penilitian ini bertujuan untuk mengkaji pandangan perempuan generasi Z mengenai fenomena “marriege is scary” yang mencerminkan apa saja kekhawatiran mereka dalam pernikahan. Pendekatan dalam penelitian ini adalah kualitatif dengan metode naratif. Peneliti mewawancarai 10 mahasiswi program studi Bimbingan dan Konseling Universitas Muhammadiyah Prof. DR. HAMKA sebagai responden. Peneliti  menanyakan makna pernikahan, isu yang membuat mereka khawatir akan pernikahan dan pandangan mereka tentang fenomena “marriage is scary”.  Hasil dari penilitian menunjukkan bahwa pandangan positif perempuan generasi Z terhadap pernikahan, yaitu sebagai komitmen yang penuh dengan tantangan dan kekhawatiran terhadap kekerasan yang mungkin akan terjadi serta budaya patriarki yang kian meluas. Selain dari itu perempuan generasi Z juga menghargai pernikahan sebagai wadah untuk pertumbuhan pribadi dan hubungan yang saling mendukung. Kekahawatiran dalam sebuah pernikahan yang dimiliki baik yang bersumber dari dalam diri dan luar diri mereka. Fenomena yang kian berkembang soal “marriage is scary” memperkuat rasa khawatir mereka dan makin mendorong mereka untuk lebih memilih dalam mencari pasangan juga lebih memantapkan mental untuk menuju jenjang pernikahan. Implikasi pada bimbingan dan konseling pranikah adalah diperlukannya layanan preventif yang dapat menyelesaikan kekhawatiran akan permasalahan dalam pernikahan.